2015
DOI: 10.1002/smll.201570077
|View full text |Cite
|
Sign up to set email alerts
|

Immunoengineering: Biodegradable Nanoellipsoidal Artificial Antigen Presenting Cells for Antigen Specific T‐Cell Activation (Small 13/2015)

Abstract: Nonspherical ellipsoidal nanodimensional artificial antigen‐presenting cells (aAPCs) are fabricated by J. J. Green and co‐workers and on page 1519 they are shown to have superior T‐Cell activation and pharmacokinetic properties compared to equivalent spherical nanodimensional aAPCs. Shown on the cover are transmission electron microscopy images of the ellipsoidal nanoparticles interacting with a computer generated T‐Cell membrane as nano aAPCs. Due to their larger radius of curvature, ellipsoidal nano aAPCs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One strategy relies on elongating aDCs into an elliptical shape, which has shown higher immunogenicity and superior pharmacokinetic properties in vivo compared to spherical aDCs. [47] Figure 5. Schematic diagram of the distance between T cells and aDCs of ≈15 nm, which must be achieved upon TCR triggering.…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…One strategy relies on elongating aDCs into an elliptical shape, which has shown higher immunogenicity and superior pharmacokinetic properties in vivo compared to spherical aDCs. [47] Figure 5. Schematic diagram of the distance between T cells and aDCs of ≈15 nm, which must be achieved upon TCR triggering.…”
Section: Morphologymentioning
confidence: 99%
“…One strategy relies on elongating aDCs into an elliptical shape, which has shown higher immunogenicity and superior pharmacokinetic properties in vivo compared to spherical aDCs. [ 47 ] Sunshine et al compared elliptical and spherical aDCs and concluded that increasing the aspect ratio (up to 6.6) led to improved antigen‐specific activation of CD8 + T cells, reduced tumor burden and increased survival. These results seem to be due to increased interaction along the long axis of elliptical aDCs with T cells ( Figure A).…”
Section: Development Of Adcs Inspired By Their Natural Counterpartsmentioning
confidence: 99%